2001
DOI: 10.1103/physrevlett.86.4255
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Spin-Orbit Splitting inΛSingle-Particle States

Abstract: The spin-orbit splitting of Lambda single-particle states in (13)(Lambda)C was measured. The 13C(K-,pi(-))(13)(Lambda)C reaction was used to excite both the 1/2(-) and 3/2(-) states simultaneously, which have predominantly 12C(0(+)) x p(Lambda) configuration. gamma rays from the states to the ground state were measured in coincidence with the pi(-)'s, by which ls splitting was found to be 152+/-54(stat)+/-36(syst) keV. The value is 20-30 times smaller than exhibited by the ls splitting in the nuclear shell mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
59
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(70 citation statements)
references
References 25 publications
11
59
0
Order By: Relevance
“…From this spin assignment, the previous result for the Λ-spin-dependent spin-orbit force parameter of −0.02 < S Λ < 0.03 MeV [7] was improved to −0.02 < S Λ < −0.01 MeV. This sign of the Λ-spin-dependent spinorbit term is consistent with the p 1/2 − p 3/2 spin-orbit splitting in 13 Λ C measured with NaI counter arrays by the BNL E929 experiment [12].…”
supporting
confidence: 69%
“…From this spin assignment, the previous result for the Λ-spin-dependent spin-orbit force parameter of −0.02 < S Λ < 0.03 MeV [7] was improved to −0.02 < S Λ < −0.01 MeV. This sign of the Λ-spin-dependent spinorbit term is consistent with the p 1/2 − p 3/2 spin-orbit splitting in 13 Λ C measured with NaI counter arrays by the BNL E929 experiment [12].…”
supporting
confidence: 69%
“…The energy splitting between these states is as small as 199 keV, which reflects mainly the spin-orbit splitting of Λ hyperon in the p 3/2 and p 1/2 states. The obtained splitting is in a good agreement with the empirical value, 152±54±36 keV [18].…”
Section: Application To the 13 λ C Hypernucleussupporting
confidence: 78%
“…Sophisticated AMD calculation [14] has shown that the low-lying states of 12 C have a mixed nature between the 0p 3/2 subshell closure configuration and the 3α cluster structure, and the mixing strength is different for each state. Since the particle changes the deformation and spin properties of 12 C, it will have influence on the N spin-orbit splitting of 13 C [38][39][40].…”
Section: B Discussion On Each Hypernucleusmentioning
confidence: 99%